2015
DOI: 10.1111/jcmm.12396
|View full text |Cite
|
Sign up to set email alerts
|

LRP5 deficiency down‐regulates Wnt signalling and promotes aortic lipid infiltration in hypercholesterolaemic mice

Abstract: Low-density lipoprotein receptor-related protein 5 (LRP5) is a member of the LDLR family that orchestrates cholesterol homoeostasis. The role of LRP5 and the canonical Wnt pathway in the vascular wall of dyslipidaemic animals remains unknown. In this study, we analysed the role of LRP5 and the Wnt signalling pathway in mice fed a hypercholesterolaemic diet (HC) to trigger dyslipidaemia. We show that Lrp5−/− mice had larger aortic lipid infiltrations than wild-type mice, indicating a protective role for LRP5 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Badimon’s group demonstrated that LRP5 inhibits aortic macrophage infiltration and inflammatory cytokine production in mice fed diets that induce hypercholesterolemia [66]. The mechanism is not completely understood, but may relate to LRP5-dependent promotion of an anti-inflammatory macrophage phenotype [67].…”
Section: Introductionmentioning
confidence: 99%
“…Badimon’s group demonstrated that LRP5 inhibits aortic macrophage infiltration and inflammatory cytokine production in mice fed diets that induce hypercholesterolemia [66]. The mechanism is not completely understood, but may relate to LRP5-dependent promotion of an anti-inflammatory macrophage phenotype [67].…”
Section: Introductionmentioning
confidence: 99%
“…17 This effect was surprising since Wnt signaling in the vascular smooth muscle cell (VSMC) is implicated in stimulating osteoblastic transition and vascular calcification. 35, 36 However, recent studies demonstrate that inhibition of Wnt signaling stimulates lipid accumulation in atherosclerotic plaques, 37 and that Dkk1 mediated inhibition of aortic Wnt7b stimulates smad mediated aortic endothelial-mesenchymal transition (EndMT) and vascular calcification. 38 EndMT is a developmental physiologic process involved in the development of the cardiac valves, the cardiac septum and the aortic root, 39, 40 and it may 41 or may not 42 contribute to cardiac fibrosis in various adult disease states.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of LRP5 to cholesterol metabolism was previously suggested by the observation that ApoE −/− LRP5 −/− mice have larger atherosclerotic lesions than their ApoE −/− littermates 74. Beyond its role in promoting lipid internalization, increased expression of LRP5 also induces the activation of canonical Wnt signalling 22, 31. In macrophages, canonical Wnt signalling is thought to promote cell motility through a β‐catenin‐dependent mechanism 75.…”
Section: Discussionmentioning
confidence: 97%
“…Our group has shown that LRP5 is involved in monocyte differentiation into macrophage [30] and is up-regulated in macrophages exposed to agLDL [22]. In vivo analyses in Lrp5 À/À mice fed a hypercholesterolaemic (HC) diet showed that LRP5 deficiency increases the development of aortic atherosclerotic lesions, suggesting an atheroprotective role for LRP5 [31,32]. LRP5 belongs to the LDL receptor superfamily and shares common motifs including LDLR type A repeats, EGF-like domains and transmembrane anchors.…”
Section: Introductionmentioning
confidence: 99%